Narratives, nations, and other world products in the making of global history - Adelman, Jeremy; Eckert, Andreas (Bloomsbury Academic, 2024)
From the Enlightenment forward, the nation and other global concepts have been conjured and repurposed to manage and make sense of what we now call globalisation. The authors in this volume show how social categories such as empire, race and labour were the centerpiece subjects of collective narratives.